(untitled) (Historia, 2021)
1. H . Bley: South-West Africa under German Rule 2. V . H . H . Green: The Later Plantagenets 3. A . L . Harrington: The Great Trek and S . B . Spies: The Origins of the Anglo-Boer War 4. H . W . J . Picard: Man of Constantia 5. G . F . Bass: Geschiedenis van de scheepvaart 6. H . F . Varion: Some African Milestones 7. J . du P . Scholtz: Boonzaaier en Pieter Wenning 8. C . Pama: Cape Town . Historic Houses 9. W . P . Coolhaas: Het Huis "De Dubbele Arend" 10. A . M . Meyerman: Adriaen van der Werff 11. Van Stamvenvante Bodem deur dr . J . Ploeger